Long‐term weather, streamflow, and water chemistry datasets for hydrological modelling applications at the upper La Salle River watershed in Manitoba, Canada. (1st April 2019) - Cordeiro, Marcos R. C.; Vanrobaeys, Jason A.; Wilson, Henry F.
Abstract: Long‐term weather (1990–2013), streamflow (1990–2013; excluding 7 years with no or poor data), and water chemistry (2009–2013) datasets for hydrological modelling applications were developed using simple methods for the upper La Salle River watershed, in Canada, to address the lack of such datasets in the northern Red River Basin. Weather variables consist of temperature, relative humidity, wind speed, solar radiation, and precipitation disaggregated to an hourly time‐step. The only hydrometric variable included in the dataset is stream discharge in a daily time‐step. Water chemistry data consisted of total nitrogen (TN), total dissolved nitrogen (TDN), total phosphorus (TP), and total dissolved phosphorus (TDP). Samples were collected weekly during the open water season at the same site as the hydrometric gauging station from August 2009 to October 2012 with some gaps (i.e. Fall 2011, Spring 2012, September 2012). In 2013 the sampling frequency was increased to daily or sub‐daily during high stream discharge and weekly during low stream discharge. A data overview indicates values within ranges reported for the area. Mean annual, winter, and summer temperatures were 3.5, −10.7, and 17.2°C, respectively. Annual relative humidity averaged 73.1% but was higher and more homogenous in cold seasons. Wind speed was similar over the year with annual average of 4.3 m/s. Solar radiation followed the typical curve reported for western Canada, with peak daily average values around 250 W/m 2 in July. Precipitation records were mostly comprised of dry hours with 75.3% of the events being equal or less than 2 mm/h. Stream discharge was typical of the Canadian Prairies; the average peak discharge over the entire period was larger in April (2.3 m 3 /s) due to large amounts of snowmelt runoff. Average concentrations of TN, TDN, TP, and TDP of 1.54, 1.35, 0.56, and 0.49 mg/L, respectively, were in agreement with values found in previous studies at the site. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://doi.org/10.23684/odi-2017-00957 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .